Multifunctional management of mountain forests - Compromises between the protection and conservation functions - FUHR, Marc; CLOUET, Nicolas; CORDONNIER, Thomas; CORDONNIER, Thomas (Sciences, Eaux & Territoires, 2011)
How can the balance between protection against natural hazards and biodiversity conservation be determined at each stage in forest development? This study provides a number of answers in view of improving multifunctional management.